Visual outcomes and spectacle independence of a non-diffractive wavefront-shaping intraocular lens in post-LASIK patients - Fan, Wei; Zhu, Meiyi; Zhang, Guangbin (Frontiers in Medicine, 2025)
PurposeTo compare visual outcomes, depth of field (DOF), spectacle independence, and patient satisfaction of cataract patients with and without previous myopic laser in situ keratomileusis (LASIK) surgery who received a non-diffractive extended range-of-focus (EROF) intraocular lens (IOL).Setting:Xiamen Eye Center, Xiamen, China.DesignProspective case series.MethodsA total of 50 eyes of 41 patients implanted with the Vivity IOL were divided into Post-LASIK and Virgin groups. Outcome measures included uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), uncorrected intermediate visual acuity (UIVA), uncorrected near visual acuity (UNVA), refractive outcomes, defocus curves, subjective DOF, spectacle independence, and Visual Function questionnaire (VF-14) after 3 months postoperatively.ResultsPostoperatively, 70% of the Post-LASIK and 86.7% of the Virgin group had refractive error within ± 0.50 D (P = 0.28). The majority of both groups achieved 20/25 or better UDVA, with no significant differences between groups for UDVA, CDVA and UIVA (P > 0.05). The UNVA was significantly better in the Post-LASIK group (0.31 ± 0.08 logMAR) than Virgin group (0.45 ± 0.10 logMAR, P < 0.001). The Post-LASIK group showed a smoother curve with a wider landing area, and better subjective DOF compared to the Virgin group (P < 0.001). Spectacle independence at near ranges in bright light was higher in the Post-LASIK group (81.3 % vs 48 %, P = 0.033). Both groups reported high visual satisfaction, but the Post-LASIK group had fewer difficulties with near-distance tasks in the VF-14 questionnaire.ConclusionIn post-LASIK eyes, this wavefront-shaping EROF IOL was well-tolerated and provided an extended range of vision with significantly better UNVA, fewer difficulties in daily activities and higher spectacle independence for near vision compared to normal eyes.